Eosinophils and pleural macrophages counter regulate IL-33-elicited airway inflammation via the 12/15-lipoxygenase pathway - Ito, Emi; Hayashizaki, Reika; Hosaka, Takuro; Yamane, Tsuyoshi; Miyata, Jun; Isobe, Yosuke; Arita, Makoto (Frontiers in Immunology, 2025)
IntroductionFatty acid metabolism plays a crucial role in regulating airway inflammation through the synthesis of lipid mediators. We have previously demonstrated that a 12/15-lipoxygenase (12/15-LOX or Alox15)-derived mediator attenuates IL-33-induced eosinophilic airway inflammation in mice. However, the cellular sources of these mediators remain unclear.MethodsTo identify the cellular sources, we used several cell type-specific conditional 12/15-LOX-deficient mice.ResultsWe found that eosinophils and pleural macrophages were the major 12/15-LOX-expressing cell types responsible for attenuating airway inflammation. Eosinophils were the major population of 12/15-LOX-expressing cells found in inflamed lung tissue. In addition, pleural macrophages were the major population of 12/15-LOX-expressing cells in the thoracic cavity and were found to translocate into inflamed lung tissue in response to airway inflammation.DiscussionThis study suggests that eosinophils and pleural macrophages cooperatively regulate eosinophilic airway inflammation via 12/15-LOX expression. Targeting 12/15-LOX metabolism in these cells may offer new therapeutic strategies for severe asthma.